Trajectory patterns and factors influencing perinatal fatigue among Chinese women from late pregnancy to 6 months after delivery - Zhu, Xiaoxiao; Xia, Haiou (PeerJ, 2022)
Background Perinatal fatigue among women is related to the clinical outcomes of mothers and infants. Perinatal fatigue changes over time, and the trajectory varies according to the predictors and outcomes of the mothers. This, however, has not been documented in any study. Objectives This study aimed to identify and characterize the trajectory patterns of perinatal fatigue among women from late pregnancy to 6 months after delivery. Methods We used growth mixture modeling to estimate the trajectory of perinatal fatigue at 28 gestational weeks (T0), 37 gestational weeks (T1), 3 days (T2), 1 week (T3), 6 weeks (T4), and 6 months (T5) after delivery with (n = 1,030). The Mann-Whitney U test and binary logistic regression were used to tie the selected trajectory classes to predictors and outcomes. Results There were two distinct patterns of perinatal fatigue in women: “persistently high” (11.1%, n = 114) and “persistently low” (88.9%, n = 916). Levels of perinatal fatigue among women in the “persistently high” group were higher than those in the “persistently low” group across the six measurements. Complications, fatigue at T0, and employment status in late pregnancy were all significant predictors of trajectories. Additionally, the “persistently high” group had a greater prevalence of difficult baby care and weight retention and a lower prevalence of exclusive breastfeeding. Conclusions Our study proved the heterogeneity and characteristics of perinatal fatigue among women. Future research should concentrate on developing intervention packages targeted at specific individuals in order to alleviate perinatal fatigue in women.
Keywords: Perinatal fatigue; Trajectory; Predictors; Outcomes; Growth mixture modeling; Heterogeneity